Qiyādat al-Mar’ah fī al-Ma’had al-‘Ālī al-Ḥukūmī al-Rānīrī Banda Aceh: Al-Farṣu wa al-Taḥaddīyat - Inayatillah Inayatillah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
This article is based on a research on women leadership's opportunity at IAIN Ar- Raniry, Banda Aceh and women's challenges to achieve leadership level at the Islamic educational institutions. Based on the observation, it is found that there are no formal regulations or policies that have prevented women to occupy structural and nonstructural positions. Despite that fact, no women have occupied strategic structural position or having leadership roles such as becoming the Rector or the Dean at the IAIN Ar-Raniry.DOI: 10.15408/sdi.v17i3.457